Community compensation in the context of Carbon Capture and Storage: Current debates and practices. (October 2020) - Boomsma, Christine; ter Mors, Emma; Jack, Corin; Broecks, Kevin; Buzoianu, Corina; Cismaru, Diana M.; Peuchen, Ruben; Piek, Pim; Schumann, Diana; Shackley, Simon; Werker, Jasmin
Highlights: Community compensation may foster public support for CCS by balancing local benefits and burdens. A broad academic literature review and examples of current practices help identify lessons and knowledge gaps. We offer insight in what compensation measures for CCS might look like and which pitfalls to avoid. Fit with local needs and embedment in wider public engagement strategies is key. Flexible institutionalized compensation and considering compensation for on- and offshore developments is recommended. Abstract: Societal opposition has the potential to slow down the implementation of Carbon Capture and Storage (CCS). One of the difficulties is that the perceived benefits associated with a CCS facility for local communities tend to be low compared to its perceived burdens. As is the case for other low carbon technologies, community compensation (or community benefits) has been suggested as a way to restore this perceived imbalance. A diverse literature has looked into the role of community compensation across various land uses and research fields. Synthesis is limited, while at the same time, the provision of community compensation in practice is moving from an ad hoc to a more institutionalized approach. Therefore, it is important to take stock of the literature. This paper provides a review of the community compensation literature in the form of four debates, drawing together environmental social science research on different low carbon technologies (e.g. CCS, renewable energy). In addition, current practices in community compensation for four European countries are discussed. The two parts of this paper are brought together in a set of lessons for the provision of community compensation for future CCS projects; in turn, suggestions for further research are made to address remaining knowledge gaps.